Inference of sigma factor controlled networks by using numerical modeling applied to microarray time series data of the germinating prokaryote - Strakova, Eva; Zikova, Alice; Vohradsky, Jiri (Nucleic acids research, 2014)
A computational model of gene expression was applied to a novel test set of microarray time series measurements to reveal regulatory interactions between transcriptional regulators represented by 45 sigma factors and the genes expressed during germination of a prokaryote Streptomyces coelicolor. Using microarrays, the first 5.5 h of the process was recorded in 13 time points, which provided a database of gene expression time series on genome-wide scale. The computational modeling of the kinetic relations between the sigma factors, individual genes and genes clustered according to the similarity of their expression kinetics identified kinetically plausible sigma factor-controlled networks. Using genome sequence annotations, functional groups of genes that were predominantly controlled by specific sigma factors were identified. Using external binding data complementing the modeling approach, specific genes involved in the control of the studied process were identified and their function suggested.
Keywords: genetická transkripce; Streptomyces coelicolor; spory bakteriální; sigma faktor; Oligonucleotide Array Sequence Analysis; Transcription, Genetic; genové regulační sítě; Computer Simulation; Sigma Factor; Gene Regulatory Networks; regulace genové exprese u bakterií; Kinetics; počítačová simulace; Spores, Bacterial; modely genetické; stanovení celkové genové exprese; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Gene Expression Regulation, Bacterial; Models, Genetic; Gene Expression Profiling; kinetika